Numeracy skills for business - Curwin, Jon.; Slater, Roger (London : Chapman and Hall, 1994)
What is numeracy? Describing situations. Collecting data. Forecasting. Models. Uncertainty. Reflections.
Keywords: Statistics; Business mathematics; Statistics; Business mathematics